Chemical and mineralogical characterization of the Mineo (Sicily, Italy) pallasite: A unique sample. (23rd November 2017) - Zucchini, A.; Petrelli, M.; Frondini, F.; Petrone, C. M.; Sassi, P.; Di Michele, A.; Palmerini, S.; Trippella, O.; Busso, M.
Abstract: The Mineo pallasite is characterized here for the first time. The only 42 g still available worldwide is part of the collection of the Department of Physics and Geology, University of Perugia. A multianalytical approach was used, joining field‐emission scanning electron microscopy, Raman analysis, X‐ray powder diffraction, electron‐probe microanalysis, and laser ablation inductively coupled plasma mass spectrometry. Results highlighted that (1) the Mineo pallasite belongs to the Main Group pallasites; (2) the silicate component is essentially olivine, with no pyroxene component; (3) the olivine chemical composition varies in terms of both iron and trace elements; (4) the metal phase is essentially kamacite with the taenite mainly found in the plessite structure; (5) phosphide phases are present as schreibersite and barringerite. The observed compositional variability in olivines as well as their occurrence as both angular and rounded crystals suggest that the Mineo pallasite could have been derived from a large impact of a differentiated parent body with a larger solid body. The resulting pallasite conglomerate consists of the compositionally different olivines, likely coming from different areas of the same differentiated parent body, and the residual molten Fe‐Ni.